Insights from UNCCD COP 16: A transition to more sustainable extensive livestock production - Onyango, Polycarp Otieno (CGIAR System Organization, 2024)
A CGIAR-hosted side event on sustainable extensive livestock production at the UNCCD COP 16 in Riyadh, Saudi Arabia has highlighted the vital role of livestock in global nutrition, particularly in low- and middle-income countries. Session participants noted that climate change mitigation in grazing systems requires tailored, site-specific solutions, equitable approaches, and investment in innovation. They remarked that proven practices like improving animal health and enhancing breeding can offer significant benefits for people and the planet, noting that to ensure a just transition for livestock-dependent communities, needs investments to close efficiency gaps and support innovative solutions. Together they called for collaboration among governments, researchers, and livestock keepers as an essential component for durable outcomes.